(untitled) (Raparin Journal of Humanities (RJH), 2020)
Haggard’s Ayesha is the continuation of the Victorian dream novel She. H. Rider Haggard’s She, subtitled A History of Adventure, is figured to be among top rated books at any point distributed: it had sold exactly 83 million duplicates by 1965. Ayesha (really articulated ’Assha’), subtitled The Return of She, who takes after She in the book, is an amazing and puzzling white sovereign who administers the African Amahagger individuals. Ayesha has enchantment controls and is undying, which makes She a dream experience book. Despite the fact that She and Ayesha were distributed almost twenty years separated, H. Rider Haggard stated that Ayesha was a decision to a two-section book, not a continuation. There is likewise a "prequel," She and Allan (1921). In the two books, an imaginary manager shows an original copy portrayal by Ludwig Horace Holly. In Haggard’s She, considering that some parts of the novel are so comfortable, readers might feel compelled into thinking that they are going through Haggard’s tour in Africa. Fortunately, in any event, when the plot eases back to a nearly gastropod pace, the way Haggard’s depicts the African culture and scene conveys the reader along. Ayesha, known as She-Who-Must-Be-Obeyed, first showed up in sequential structure from 1896 to 1897 in the novel She. Ayesha is one of the marvelous, kick-ass lady characters in Victorian writing who represents the misogynist construction of femininity and embodies the femme fatale. This paper is principally concerned about the representation of feminine power and the representation of womanhood in Haggard’s Ayesha. Some questions will be investigated here. Can one consider Ayesha as a “conclusion” or a “sequel” to She since the whole novel replicates the same thematic and structural maneuvers of She? Does Haggard revive Ayesha, the “new woman”, in The Return of She respond to the threat to traditional gender roles? The findings of this study will be beneficial for the researchers, and all the undergraduate and postgraduate students of English department.